Kebijakan Pendidikan Profesi Guru (PPG) Transformatif Plus terhadap Lulusan Pendidikan Guru Madrasah Ibtidaiyah - Shulhan, Shulhan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The study discusses the Teacher Professional Education (PPG) Transformation Plus policy for Madrasah Ibtidaiyah Teacher Education (PGMI) graduates. The teaching profession's responsibility to educate and develop characters is similar to the medical profession for caring for human health. Both require special expertise through academic education and professional education. The research used qualitative methods in library research. The source was a letter attachment from the Directorate General of Islamic Education of the Ministry of Religious Affairs with number B-36/DJ.I/Dt.I.II/HM.00/01/2025. Researchers used content analysis techniques in three stages: planning, organizing, and reporting. The findings are as follows: First, the allowance of non-PGMI/PGSD education majors to become class teachers minimizes the acceptence of PGMI graduates. These majors can become classroom teachers, which is the work area of PGMI graduates, but PGMI graduates cannot become subject teachers. Secondly, this policy weakens the bargaining value of PGMI majors because the classroom teacher profession does not have to be from a PGMI undergraduate.